Функціонально-семантичні особливості воєнної лексики в інтернет-виданнях - Голопич, І. М.; Holopych, I. M.; Перцева, В. А.; Pertseva, V. A. (Наукові записки [Центральноукр. держ. пед. ун-ту імені Володимира Винниченка]. Сер.: Філологічні науки. – 2023. – Вип. 2(205). - С. 45-50, 2023)
Розглянуто функціонально-семантичне поле «війна» й особливості вживання воєнної лексики в текстах інтернет-видань. Досліджено процеси реалізації функціонально-семантичних особливостей воєнної лексики в текстах інтернет-видань. Акцентовано увагу на лексичних одиницях, які використовуються в концептуалізації універсального поняття «війна»; проаналізовано функціонально-семантичні особливості лексем, що відтворюють воєнні дії та їх компоненти; виокремлено лексичні одиниці, які реалізуються в репрезентації воєнних дій в Україні й, попри їх нейтральні або політичні значення, належать до воєнної лексики.

The article analyzes the functional and semantic field of “war” based on the texts of online publications. The purpose of the work is to study the processes of realization of functional and semantic features of military vocabulary in the modern Ukrainian language, namely in the texts of online publications. In accordance with this goal, the authors of the article define specific research objectives: to identify the inventory of lexical items used in the conceptualization of the studied concept of “war”; to describe the functional and semantic features of lexical items representing military actions and components; to single out lexical items that are used in the representation of military actions in Ukraine and which, despite their neutral or political meanings, can be classified as military vocabulary. The object of the study is military vocabulary, and the subject is its functional and semantic features. The material for the analysis was based on examples obtained by the method of continuous sampling from the texts of Ukrainian websites in 2020–2023. The study of the factual material was conducted using a set of methods, including, in particular, contextual analysis and the method of linguistic interpretation of language units. According to the results of the study, military vocabulary is a multidimensional mental formation, the content of which is formed by conceptual and figurative components. It is proved that in the center of the functional and semantic field “war” is the noun “war”, the near periphery of which is represented by synonyms of this word, and the far periphery – by vocabulary denoting Ukrainian and world politics, world security institutions, as well as units denoting weapons and military equipment. The semantic core of such vocabulary is the concept of “war”, which includes nominative units of the near periphery in various synonymous forms. Nominative units of the far periphery of the functional-semantic field “war” are represented by lexemes denoting weapons, equipment, actions, toponyms, positions of Ukrainian and world politics, as well as various political, security, judicial, military organizations, institutions. The concept of “war” is explicated by a large number of lexical units of various structures (derivatives, composites, prepositional constructions, metaphor-metonymic formations), which are used to represent the functional-semantic field of “war” depending on the profiling feature or units indicating implementation, conduct, execution war The analyzed linguistic units perform nominative, expressive and metonymic functions in the texts of online publications.

Рассмотрены функционально-семантическое поле «война» и особенности употребления военной лексики в текстах интернет-изданий. Исследованы процессы реализации функционально-семантических особенностей военной лексики в текстах интернет-изданий. Акцентировано внимание на лексических единицах, используемых в концептуализации универсального понятия "война"; проанализированы функционально-семантические особенности лексем, воспроизводящие военные действия и их компоненты; выделены лексические единицы, реализуемые в репрезентации военных действий в Украине и, несмотря на их нейтральные или политические значения, относятся к военной лексике.
Functional-semantic features of military vocabulary in online publications
Keywords: функціонально-семантичне поле; сучасна українська мова; інтернет-видання; воєнна лексика; неологізми; метонімізація; топоніми; functional-semantic field; modern Ukrainian language; internet edition; military vocabulary; neologisms; metonymization; toponyms; функционально-семантическое поле; современный украинский язык; интернет-издание; военная лексика; неологизмы; метонимизация; топонимы